INTERAKSI PESANTREN DAN POLITIK HUKUM ISLAM DALAM PENGUATAN SISTEM PENDIDIKAN ISLAM NASIONAL - Ichwan ahnaz Alamudi; Rabiatul Afwaliah (Darussalam, 2026)
The spread of Islam through education began with the establishment of pesantren founded by scholars and religious leaders, which have contributed significantly to the development of Indonesian society. Today, students who study Islam in these institutions, known as santri, receive not only religious education but also general knowledge that equips them to face contemporary challenges. This article aims to explain and explore the role of pesantren in the development of Indonesian society. As Islamic educational and training institutions, pesantren are responsible for educating the Muslim community and developing knowledgeable human resources grounded in strong faith and morality. Beyond serving as centers of education, pesantren also function as social institutions and hubs of religious mission activities. They play an important role in shaping and nurturing national leadership and actively participate in political life. Moreover, pesantren contribute to community economic empowerment through various programs such as cooperatives, Islamic financial institutions, and entrepreneurship training. These efforts align with Islamic teachings that emphasize the importance of poverty alleviation and strengthening the economic welfare of the community.